ENVIRONMENTAL PROBLEMS OF THE MINING INDUSTRY - Yarboboev, Tulqin Nurboboevich; Qosimova , Karima Yodgor qizi (Innovative Development in Educational Activities, 2023)
The article examines the factors affecting the environment as a result of the activities of various branches of the mining industry, and their negative consequences. Recommendations are given to improve the reduction of the impact of the mining industry on the environment.